2014
DOI: 10.4236/ajps.2014.525386
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Leaf Rust and Brown Eyespot in Genotypes of <i>Coffea arabica</i> L. Cultivated with High Plant Density

Abstract: This study investigated the severity of leaf rust and brown eyespot in genotypes of Coffea arabica L. cultivated with high plant density in the region of Caparaó-ES. The experiment was conducted in a competition field, cultivated with high plant density (8333 plants per hectare), following a randomized block design, with 16 genotypes and four replications. The plants were evaluated during consecutive harvests to study two complete reproductive cycles (from 2010 to 2012). Data were obtained for the phenological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
7
0
5
Order By: Relevance
“…In the region where this experiment was developed, the main coffee diseases are the leaf rust and the brown-eye spot, both caused by a fungus (Hemileia vastatrix and Cercospora coffeicola, respectively). Rodrigues et al (2014b) have shown that, by following the occurrence of leaf spots in plagiotropic branches of C. arabica, it is possible to identify different levels of genotype resistance to certain diseases occurring in high density cultivation systems. Genotypes with high genetic resistance to the leaf rust fungus have been observed in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the region where this experiment was developed, the main coffee diseases are the leaf rust and the brown-eye spot, both caused by a fungus (Hemileia vastatrix and Cercospora coffeicola, respectively). Rodrigues et al (2014b) have shown that, by following the occurrence of leaf spots in plagiotropic branches of C. arabica, it is possible to identify different levels of genotype resistance to certain diseases occurring in high density cultivation systems. Genotypes with high genetic resistance to the leaf rust fungus have been observed in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Most coffee in Brazil is produced in this region and each of the three farms from which samples were collected for this study grew the same coffee variety, the Coffea arabica L., (cultivar Red Catuai, IAC-44) a breed developed by the Campinas Agronomy Institute (IAC in Portuguese) for higher yield in Brazilian soil and climate conditions [ 31 , 32 ] and higher resistance to fungal diseases [ 33 , 34 ]. Even though each farm has belonged to the same respective family for at least 3 generations, each showed a distinct method of farming practice.…”
Section: Methodsmentioning
confidence: 99%
“…The estimative of genetic parameters shows the existence of considerable variation between genotypes for both systems. Genotypic differences causing expressions of different agronomic traits in C. arabica have been widely reported, such as for biometry of reproductive branches (Rodrigues et al, 2014a), nutritional parameters (Martinez et al, 2011;Moura et al, 2015;Martins et al, 2015;Rodrigues et al, 2015), resistance of plant diseases (Sera et al, 2010;Del Grossi et al, 2013;Rodrigues et al, 2014b;Shigueoka et al, 2014), drought tolerance (DaMatta, 2004;Nardini et al, 2014), and crop yield (Carvalho et al, 2012;Rodrigues et al, 2014c).…”
Section: Genetic Variability Among Genotypes In the Rainfed Farming Smentioning
confidence: 99%